2022
DOI: 10.3991/ijet.v17i14.30393
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Experiences of E-learning Practices During COVID-19: A Qualitative Study

Abstract: COVID-19 pandemic has disrupted schooling globally. Affecting millions of students, the conventional face-to-face (F2F) education system has been replaced by e-learning overnight. As the advantages, disadvantages, and technical challenges of this abrupt transformation were already well-documented, this study aimed to intensely scrutinize university students' experiences of e-learning practices in this new normal situation. Methods: Adopting the Interpretative Phenomenological Analysis (IPA), a smaller sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…On the other hand, many families faced challenges in terms of organizing the necessary information technology infrastructure such as laptops, internet connection etc., for their children to undergo online education (Bokayev, Torebekova, Davletbayeva, & Zhakypova, 2021). Sarker et al (2022) observed that it is important for parents to maintain a positive collaboration with their wards while the online learning process to make them more effective. Sedibe and Fourie (2018) observed that the academic development of students is positively influenced by the support provided by the parents.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…On the other hand, many families faced challenges in terms of organizing the necessary information technology infrastructure such as laptops, internet connection etc., for their children to undergo online education (Bokayev, Torebekova, Davletbayeva, & Zhakypova, 2021). Sarker et al (2022) observed that it is important for parents to maintain a positive collaboration with their wards while the online learning process to make them more effective. Sedibe and Fourie (2018) observed that the academic development of students is positively influenced by the support provided by the parents.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Alfaifi and Saleem (2022) note that FCM approach does not help learners to lower their language learning anxiety levels. Sarker et al (2022), for instance, in a survey, note that students' experiences with e-learning (which is similar to FCM approach) are generally unfavorable. Some researchers report that students quite often do not watch videos before the class and, as a result, the in-class activities become boring and too challenging for them (Loo et al, 2016).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…However, online learning could not solve all problems connected with the ban of face-to-face learning. For example, findings of Sarker et al [18] reveal that most of students had unfavorable experiences with e-learning. A majority of them felt that e-learning ruined their social relationships by isolating them from their peers and instructors.…”
Section: Introductionmentioning
confidence: 99%